Impact of gestational diabetes on depression and breastfeeding self-efficacy in the postpartum period in a selected hospital of Bhubaneswar - Tanupama Karna; Kalyani Rath; Anusuya Behera (Journal of Family Medicine and Primary Care)
Background: Gestational diabetes mellitus (GDM) is the most common medical complication and metabolic disorder of pregnancy. The prevalence of GDM in all pregnancies is approximately 7%. Globally, there are 14% pregnancies with significant variability in prevalence based on diagnostic criteria, sociodemographic characteristics, and geographic region. Objectives: The aim of this study was to determine the level of depression, breastfeeding self-efficacy, and association of depression among postnatal GDM and non-GDM mothers. Methods: This cross-sectional descriptive study was conducted in the Obstetric and Gynaecology ward of KIMS hospital using a consecutive sampling technique. Out of 200 postnatal mothers, 100 GDM and 100 non-GDM postnatal mothers were recruited. Data were collected using a the self-structured demographic tool, Edinburgh postnatal Depression Scale, and Breastfeeding Self-efficacy Scale. Written informed consent was taken from the postnatal women before data collection. The inclusion criteria included postnatal women who were willing to participate and understand and respond in Odia or English, and postnatal women who have chronic diseases like tuberculosis, malignancy, renal failure, and cardiac disorder were excluded from the study. Results: The depression of mothers with GDM was found higher compared to non-GDM mothers, and breastfeeding self-efficacy was lower in GDM and higher in non-GDM mothers. Conclusion: In the current study, it has been concluded that the depression level of mothers with GDM was found higher compared to non-GDM mothers and breastfeeding self-efficacy was lower in GDM as compared to non-GDM mothers. GDM mothers have a significant impact on depression and breastfeeding self-efficacy during the postpartum period.